Bandwidth Reduction via Localized Peer-to-Peer (P2P) Video - Ken Kerpez; Yuanqiu Luo; Frank J. Effenberger (International Journal of Digital Multimedia Broadcasting)
This paper presents recent research into P2P distribution of video that can be highly localized, preferably sharing content among users on the same access network and Central Office (CO). Models of video demand and localized P2P serving areas are presented. Detailed simulations of passive optical networks (PON) are run, and these generate statistics of P2P video localization. Next-Generation PON (NG-PON) is shown to fully enable P2P video localization, but the lower rates of Gigabit-PON (GPON) restrict performance. Results here show that nearly all of the traffic volume of unicast video could be delivered via localized P2P. Strong growth in video delivery via localized P2P could lower overall future aggregation and core network bandwidth of IP video traffic by 58.2%, and total consumer Internet traffic by 43.5%. This assumes aggressive adoption of technologies and business practices that enable highly localized P2P video.